Involvement of envelope-glycoprotein glycans in HIV-1 biology and infection - Raska, Milan; Novak, Jan (Archivum immunologiae et therapiae experimentalis, 2010)
Infection of host cells with HIV-1 depends on a highly glycosylated virus envelope glycoprotein (Env) and host-cell receptors. Glycans participate substantially in Env folding and in the binding of virions to the host-cell surface and indirectly affect cellular uptake of HIV-1. Moreover, Env glycans could protect HIV-1 from host's neutralizing antibodies, but some glycans, on the other hand, represent targets for neutralizing antibodies. Variability of Env and its glycans in the HIV-1 strains from around the world as well as in patients during disease progression contributes substantially to further HIV-1 spreading in spite of the progress in basic HIV-1 research, vaccine development, and highly active antiretroviral therapy of HIV-1 infections.
Keywords: neutralizující protilátky; polysacharidy; přichycení viru; vysoce aktivní antiretrovirová terapie; vakcíny proti AIDS; virulence; HIV-1; Antiretroviral Therapy, Highly Active; HIV infekce; Antigenic Variation; proteiny virového obalu; Antibodies, Neutralizing; antigenní variace; zvířata; Humans; Virulence; Viral Envelope Proteins; Virus Attachment; AIDS Vaccines; Polysaccharides; HIV Infections; lidé; Animals